Using Virtual Learning to Develop Palliative Care Skills Among Humanitarian Health Workers in the Rohingya Refugee Response in Bangladesh. (August 2022) - Doherty, Megan; Lynch-Godrei, Anisha; Azad, Tasnim; Ladha, Fatima; Ferdous, Lailatul; Ara, Rowsan; Richardson, Kathryn; Groninger, Hunter
Background: Palliative care is an essential component of health responses in humanitarian settings, yet it remains largely unavailable in these settings, due to limited availability of palliative care training for healthcare professionals. Online training programs which connect experts to clinicians in the field have been proposed as an innovative strategy to build palliative care capacity humanitarian settings. Objective: To describe the implementation and evaluate the impact of delivering palliative care education using an established virtual learning model (Project ECHO) for healthcare clinicians working in the Rohingya refugee response in Bangladesh. Program acceptability and the impacts on learners' self-reported knowledge, comfort, and practice changes were evaluated. Methods: Using the Project ECHO model, an education program consisting of 7 core sessions and monthly mentoring sessions was developed. Each session included a didactic lecture, case presentation and interactive discussion. Surveys of participants were conducted before and after the program to assess knowledge, confidence, and attitudes about palliative care as well as learning experiences from the program. Results: This virtual palliative care training program engaged 250 clinicians, including nurses (35%), medical assistants (28%) and physicians (20%). Most participants rated the program as a valuable learning experience (96%) that they would recommend to their colleagues (98%). Participants reported improvements in their knowledge and comfort related to palliative care after participation in the program, and had improved attitudes towards palliative care with demonstrated statistical significance (p < 0.05). Conclusions: Virtual training is a feasible model to support healthcare providers in a humanitarian health response. Project ECHO can help to address the urgent need for palliative care in humanitarian responses by supporting healthcare workers to provide essential palliative care to the growing number of individuals with serious health-related suffering in humanitarian settings.